The association between Dietary Index for Gut Microbiota and sarcopenia: the mediating role of Dietary Inflammatory Index - Gong, Hongyang; Duan, Shuqin; Lin, Xiaomei; Huang, Shaoqun (Frontiers in Nutrition, 2025)
BackgroundGiven the global changes in environmental and dietary habits, understanding the potential impact of dietary factors and diet-related inflammation on skeletal muscle diseases, including sarcopenia, is crucial. Investigating these relationships can aid in the development of more effective prevention strategies. This study used the Dietary Index for Gut Microbiota (DI-GM) and the Dietary Inflammatory Index (DII) as diet-related variables. DI-GM is a scoring system used to assess the influence of diet on Gut Microbiota health. Additionally, DII quantifies the inflammatory potential of a diet. This study explores the association between DI-GM and sarcopenia and evaluates whether DII moderates this relationship.MethodsThis study conducted a cross-sectional analysis of 9,470 participants from the 2011–2018 NHANES database. Multivariable logistic regression, restricted cubic splines (RCS), and subgroup analysis were employed to examine the association between DI-GM and the prevalence of sarcopenia. Additionally, mediation analysis was performed to investigate the potential associations between DII, DI-GM, and sarcopenia.ResultsA total of 9,470 participants were included in this study, of whom 823 (7%) had sarcopenia. After adjusting for all variables using multivariable logistic regression, each one-unit increase in DI-GM was associated with a 15% decrease in sarcopenia prevalence (OR = 0.85, 95% CI: 0.77, 0.94), while each one-unit increase in DII was associated with a 28% increase in sarcopenia prevalence (OR = 1.28, 95% CI: 1.17, 1.41). Furthermore, the results remained robust when DI-GM and DII were divided into tertiles. RCS analysis revealed a significant linear relationship between DI-GM and sarcopenia. The results of the subgroup analysis also showed that the above relationships were robust. Mediation analysis showed that 55% of the association between DI-GM and sarcopenia was mediated by DII (P < 0.001).ConclusionAdhering to dietary recommendations based on DI-GM may reduce the prevalence of sarcopenia. Additionally, DII appears to mediate this relationship, suggesting that an anti-inflammatory diet could offer potential benefits.